Solution of High Order Ordinary Boundary Value Problems Using Semi-Analytic Technique - Tawfiq, Luma N. M.; Yassien, Samaher M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this paper is to present a method for solving high order ordinary differential equations with two point's boundary condition, we propose semi-analytic technique using two-point oscillatory interpolation to construct polynomial solution. The original problem is concerned using two-point oscillatory interpolation with the fit equal numbers of derivatives at the end points of an interval [0 , 1] .  Also, many examples are presented to demonstrate the applicability, accuracy and efficiency of the method by comparing with conventional methods.